Reestructuración técnico administrativa de la empresa Air Glass (2019)
First, an external and internal diagnosis was made in order to know in a more clear and precise way the current situation of the company, using tools such as the PESTAL analysis, five PORTER forces, business diagnosis of the Chamber of Commerce and Matrix DOFA In the technical study, the different products were identified, thus elaborating a detailed description of each one of these supporting it with administrative diagrams, technical data sheets and Pareto diagram. It was also carried out, the study of methods, of times and capacities of production, analysis of risks, distribution of the space and 5 S´s by way of obtaining the proposals of improvement supported by the identification of the benefits and the compared of the two scenarios . In the administrative study the strategic planning was designed where the company's organization chart was established along with the functions manual for each office, defining the processes of human talent management and by means of a salary study proposing the Salary adjustment for the identified charges. In conclusion, the financial study defined the amount of the investment required for the implementation of this project and in order to evaluate the viability of this, the cash flows projected in a five-year horizon were carried out and analyzed through Financial indicators resulting in a net present value with project of $62,486,264 with an internal rate of return equivalent to 82.2% surpassing the internal rate of opportunity established in 16.87%.